Quaternary bioactive glass-derived powders presenting submicrometric particles and antimicrobial activity - Novak, Sara (2022)
The biomedical engineering advances in the last years have been rising demand for multifunctional biomaterials. Bioactive glass (BG) submicron particles are potential candidates for the formulation of composites with improved dispersion and homogeneity between the constituents. This work presents the preparation of SiO2–Na2O–CaO–P2O5 glass-derived powders composed of particles with homogenous shapes and sizes between 300 and 500 nm. Two types of synthesis were employed for the preparation of the BG powders, the melt-quenching method, and a citric acid-assisted sol-gel route at a low citric acid concentration (0.005 mol L−1). The morphology of the particles was achieved by a low-energy process using a ball mill. These powders were characterized for their structure and surface area and evaluated for in vitro mineralization and antibacterial behavior. X-ray diffraction (XRD) analysis revealed different crystalline silicate phases in the sol-gel-derived powder and confirmed the amorphous structure of the melt-quenching-derived one. The surface of the particles was covered by hydroxycarbonate-apatite (HCA) after five days in simulated body fluid (SBF). The antibacterial activity against Staphylococcus aureus was higher for the sol-gel-derived powder, showing inhibition >99% of the bacteria growth in 24 h for all concentrations studied. These BG-based powders present a set of characteristics useful for the formulation of multifunctional composites for orthopedic applications.